One-step laser ablation synthesis of magnetic nanoparticles with carbon coating for tribological applications. (May 2023) - Piotto, Valentina; Litti, Lucio; Zin, Valentina; Meneghetti, Moreno
Abstract: Among different materials able to reduce wear and friction in tribological couplings, there are lubricant nanofluids obtained by dispersing suitable nanoparticles into a host fluid. Carbon-based nanomaterials are known to be effective additives, but their efficiency can be further improved by combination with magnetic compounds. Unfortunately, the preparation of such bifunctional materials often require complex syntheses or need post-synthesis functionalization processes, thus increasing costs and reducing reliability. Herein, a simple and cost-effective one-step synthesis method, based on laser ablation in solution, is used to produce magnetic responsive nanoparticles surrounded by a carbon matrix to be exploited as lubricating additives. The lubricating colloidal solutions are thus easily obtained without the use of surfactants nor multi-step processes, which can contaminate the final product or increase production costs. They exhibit a very good stability and reduce the wear coefficient of almost 50% in presence of an applied magnetic field in respect to the base fluid alone. The importance of the presence of the carbon matrix surrounding the magnetic core to develop a positive tribological behaviour has been proved. Graphical Abstract: ga1 Highlights: Magnetic nanoadditives can be driven with an external magnetic field towards specific action zones. Laser ablation synthesis allows producing magnetic responsive nanoparticles surrounded by a carbon matrix. The nanofluid could reduce almost two times the severity of wear phenomena. The lubricious carbon phase is confined within the tribological contact area due to the magnetic properties of nanoparticles.